Design and analysis of a dual gate tunnel FET with InGaAs source pockets for improved performance. (November 2022) - Rasheed, Gadarapulla; Sridevi, Sriadibhatla
Abstract: In this work, we propose a novel dual gate tunnel FET (TFET) with an improved ON current. The source pockets of the proposed TFET are designed with a narrow bandgap InGaAs material. As a result, the tunnel width is minimized and a large number of charge carriers will tunnel via the source-channel junction. The DC parameters, as well as RF figures of merit, are analyzed for the proposed TFET. The results have shown that the proposed TFET exhibits a 3.8x increment in ON current, a 51.75% decrement in threshold voltage, and a 50.67% reduction in the subthreshold swing as compared to the existing device. The proposed device has reported a transconductance of 15.4 mS/ μ m, an output conductance of 8.4 mS/ μ m, a cut-off frequency of 22.35 THz, and a gain-bandwidth-product of 5.11 THz at a supply voltage of 1 V. Further, temperature stability analysis is carried out to study its impact on DC parameters of the proposed TFET.